Peran Kepribadian Muhammadiyah dalam Membangun Etika Sosial dan Kebangsaan - Vitantri Vitantri; Riska Nurazila; Aulia Faradiva; Nadia Thalia Ramadhani; Wismanto Wismanto; Wira Ramashar (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The role of Muhammadiyah personality in building social and national ethics is an important theme in the context of national and state life. Muhammadiyah as an influential Islamic organization in Indonesia has a distinctive personality foundation, namely prioritizing progressive Islamic values, oriented towards education, health and social welfare. This research aims to analyze Muhammadiyah's contribution to the development of social and national ethics through its programs and activities, both in the social, educational and da'wah fields. The method used in this research is qualitative analysis using a literature study approach. The research results show that Muhammadiyah's personality which is based on the principles of progressive Islam has a significant role in building inclusive social ethics and a strong nationality, especially in maintaining national unity and integrity. In conclusion, Muhammadiyah with its personality is able to become an agent of change in encouraging harmonious social ethics and strengthening Indonesia's national identity.